Stable fabrication of femtosecond-laser-induced periodic nanostructures on glass using real-time monitoring and active feedback control - Godai Miyaji; Daisuke Nagai; Takemichi Miyoshi; Hideyuki Takada; Dai Yoshitomi; Aiko Narazaki (Light: Advanced Manufacturing)
Femtosecond laser pulses can be employed to directly form periodic nanostructures on solid surfaces, including hard materials such as diamond and sapphire, via ablation. Thus, this technique is promising for industrial nanofabrication applications. However, the stable formation of uniform nanostructures is challenging because of their high sensitivity to changes in processing conditions, such as the surface roughness of materials and laser power. Herein, we report a real-time monitoring and control approach for fabricating high-quality nanostructures on glass surfaces. We measured the reflectance and transmittance of a laser-irradiated surface simultaneously and determined their specific values corresponding to the formation of a uniform nanostructure with a period of 200 nm and depth of 1 μm. By utilising these values as feedback signals in a proportional-integral-derivative control system, we adjusted the laser power during irradiation to form a uniform nanostructure. This approach led to a significant reduction in the defect ratio of the nanostructure (~2.4%), which represents a 10-fold reduction compared with uncontrolled processing. Our results demonstrate the potential for the stable and direct fabrication of high-quality nanostructures on solids and offer a valuable method for the quality assurance of nanostructures for various applications.